EFFECTS OF SMOKELESS TOBACCO ON STOMACH - Shah, Syed Humayun; Akhtar, Saleem; Nagi, A.H. (Journal of Ayub Medical College Abbottabad, 1990)
ABSTRACT: This study was designed to see the effects of smokeless tobacco on the stomach. 40 Rabbits were distributed into four groups. One group was used as control, while the rest three were given Nasswar, water extract of tobacco, Nasswar and water extract of tobacco respectively. The animals were sacrificed and the stomach were cut and examined for changes after fixing and staining. The morphological changes produced were mild, while the degenerative changes and inflammatory infiltration were observed in some animals. In our study we could not see any carcinogenic effect of tobacco in the stomach Prolong clinical and experimental study should be canned out to determine the carcinogenic effect of Nasswar and tobacco.